Unshaved : resistance and revolution in women's body hair politics - Fahs, Breanne (University of Washington Press, 2022)
"Body hair occupies a fascinating place between the seemingly trivial and mundane, and deeply entrenched views about gender, identity, beauty, and social norms. Unshaved: Resistance and Revolution in Women's Body Hair Politics looks at the politics of hair, how it moves from a personal grooming choice to something with wide resonance in the cultural politics of reproductive rights, feminist battlegrounds, and tensions about women's "place" in society. Popularly emerging in the United States in the 1920s and becoming a compulsory practice by the late 1950s, women's body hair removal came to signify gendered expectations surrounding desirability and adult womanhood. For Fahs, body hair removal is the ultimate example of "the personal is political," as the everyday practices of women's lives intersect with stories about entitlement to women's bodies, corporate/capitalist intrusions onto the body, liberal versus radical feminist battles over bodily autonomy, and tensions about who controls bodily choices. Fahs examines resistance to body hair norms and the deeply entrenched feelings people have about body hair, incorporating historical materials and qualitative interviews to question the assumptions we make about "normal" bodies, talk about oppression, social identity, patriarchy, biopolitics, and power. Throughout, Unshaved interrogates the meanings attached to hair, the reproduction of gendered social norms, and the everyday workings of corporeal resistance"--